The International Radio Spectrum Management: A Regime Theory Analysis - Mohamed El-Moghazi; Jason Whalley (International Telecommunications Society (ITS), 2019)
The international radio spectrum management regime is one of the oldest existing regimes with the main treaty of the regime, the Radio Regulations (RR), being 113 years old in 2019. However, there have been calls that the Radio Sector of the International Telecommunication Union (ITU-R) has become irrelevant to today's wireless world. In terms of regime theory, there are three schools of international regime analysis, namely, liberalism, realism and constructivism. With this in mind, this paper's main research question is quite straightforward, to ascertain which of these three schools applies to modern international spectrum management? To achieve this, the paper adopts a qualitative inductive approach that is based on primary data collected from 58 semi-structured interviews with the main stakeholders from the ITU-R. The examination of the empirical data supports the existence of a postpositivism perspective in regime theory regarding the international spectrum management regime, where hegemonic countries have a mutual interest in having global harmonized spectrum for their technologies, standards and systems. Accordingly, they utilize their lobbying power to promote their ideas. While the regime decision-making procedures have started not to reflect advances in wireless technology, most of the regime's actors prefer to operate according to those procedures advocated by ITU-R so that they can get their technologies approved and legitimated. Unlike other international organisation (e.g., Security Council), developing countries feels more powerful in the ITU-R due to the one-vote per country rule. The ITU-R Bureau plays an important role of encouraging and reaching a compromise and providing data on the application of the RR. Finally, the paper shows that none of the three schools of theory can solely capture the essences of the international spectrum management regime. Thus, our analysis provides empirical support to a (tentative) synthesis of these schools.
Keywords: 330